Great Northern Railway : A History - Hidy, Ralph W. (Ralph Willard), 1905-1977; Hofsommer, Donovan L.; Scott, Roy Vernon, 1927-; Hidy, Muriel E. (Fesler-Lampert Minnesota heritage book series., 2014)
In the sprawling Northwest, from the upper Mississippi River valley to Puget Sound, no railroad shaped the landscape and society like the Great Northern Railway Company. This is the complete history of that enterprise, from 1856, when the first charter was granted, through the era of James J. Hill--known as the Empire Builder--to its maturation and eventual merger in 1970, when the eight-thousand-mile Great Northern was incorporated into the massive Burlington Northern. The Great Northern Railway highlights the changes brought on by economic, political, social, and technological advances, including world wars, increased competition from other modes of transportation, and tighter government restrictions. The first part of the book (1856-1916) examines the railway's early strategies and philosophy, relations with employees, and vigorous campaigns to develop the service area. The second part of the history (1916-1970) offers an assessment of a dramatic period of transition for the railroad-international conflicts, the Great Depression, the rise of motor vehicles, increasing labor costs, and stronger unions. Illustrated with more than two hundred maps, period photographs, and drawings, the volume also includes appendixes listing the original track-laying history, track removals, ruling grades on main freight routes, and main line ruling grades from Minneapolis to Seattle.